Spatial light modulators for the manipulation of individual atoms - Brandt, L; Muldoon, C; Thiele, T; Dong, J; Brainis, E; Kuhn, A (Springer-Verlag, 2011)
We propose a versatile arrangement for the trapping and manipulation of single atoms in optical tweezers formed by the direct image of a spatial light modulator (SLM). The scheme incorporates a high numerical aperture microscope to map the intensity distribution of a SLM onto a cloud of cold atoms. The regions of high intensity act as optical dipole-force traps. With a SLM fast enough to modify the trapping potential in real time, this technique is well suited for the controlled addressing and manipulation of arbitrarily selected atoms. © 2011 Springer-Verlag.